T cell responses at diagnosis of amyotrophic lateral sclerosis predict disease progression - Fang, Fang (Karolinska Institutet, 2022)
In this project, we aimed to understand how T cell responses contribute to the disease progression of amyotrophic lateral sclerosis (ALS). The present data is on single-cell sequencing isolated from human cerebrospinal fluid (CSF) cells from both ALS patients (n=5) and controls (n=4). This analysis was conducted as part of a bigger project which is summarized in the section below.

We used flow cytometry to define T cell subsets and phenotypes in blood and CSF samples collected at the time of diagnosis on a cohort of 89 newly diagnosed ALS patients in Stockholm, Sweden. High frequency of CD4+FOXP3- effector T cells in blood and CSF was associated with a poor survival whereas high frequency of activated regulatory T (Treg) cells and high ratio between activated and resting Treg cells in blood was associated with a better survival. T cell profiles also predicted disease progression rate. On an independent cohort of cases and controls we used single cell transcriptomics data to demonstrate that ALS patients had altered T cell gene expression patterns and clonally expanded CD4+ and CD8+ T cells in CSF. In summary, T cell responses contribute to disease progression of ALS, supporting modulation of adaptive immunity as a viable therapeutic option.

The data sets contain single-cell RNA sequencing data from 9 individuals (5 ALS cases and 4 controls). Immune cells were isolated from CSF. Furthermore, for each individual, we studied the T cell receptor repertoire by using V(D)J sequencing. Uploaded files are in fastq format.

För att förstå hur T-celler bidrar till sjukdomsförloppet i amyotrofisk lateralskleros (ALS), genomförde vi en kohortstudie med 89 nydiagnostiserade ALS-patienter i Stockholm, Sverige, och använde flödescytometri för att definiera T-cellspopulationer och fenotyper i blod och cerebrospinalvätska (CSF) prover insamlade vid tidpunkten för diagnos. Hög frekvens av CD4+FOXP3- effektor T-celler i blod och CSF var associerad med en försämrad överlevnad medan hög frekvens av aktiverade regulatoriska T-celler (Treg) och hög kvot mellan aktiverade och vilande Treg-celler i blod var associerad med en bättre överlevnad. T-cellsprofiler förutspådde också hur snabbt sjukdomen utvecklade sig. Encellstranskriptomikdata visade att ALS-patienter hade förändrat T-genuttryck i T-celler och förekomsten av klonalt expanderade CD4+ och CD8+ T-celler i CSF. Sammanfattningsvis bidrar T-cellssvar till sjukdomsprogression av ALS, vilket stöder modulering av adaptiv immunitet som ett genomförbart terapeutiskt alternativ.

Data innehåller RNA-sekvenseringsdata från singelceller från 9 individer (5 ALS-fall och 4 kontroller). Immunceller isolerades från CSF. Dessutom studerade vi för varje individ T-cellsreceptorrepertoaren genom att använda V(D)J-sekvensering. Uppladdade filer är i fastq-format.
T-cells svar vid diagnos av amyotrofisk lateralskleros förutsäger sjukdomsförloppet
Keywords: immune system; immunsystemet; Epidemiologic Methods; Epidemiologiska metoder; Amyotrophic Lateral Sclerosis; Amyotrofisk lateralskleros; Sequence Analysis; Sekvensanalys; Neurodegenerative Diseases; Neurodegenerativa sjukdomar; Neurogenic Inflammation; Neurogen inflammation; Immunology; Immunologi; Public Health, Global Health and Social Medicine; Folkhälsovetenskap, global hälsa och socialmedicin